Electroanalytical and Spectrophotometric Determination of N-acetyl-p-aminophenol in Pharmaceuticals - Goclik,E. (2019)
Electrochemical oxidation of N-acetyl-p-aminophenol (AAP) and selected pharmaceutical products containing AAP is described in this study. Investigations were carried out at Pt electrode, with the application of cyclic (CV) and differential pulse (DPV) voltammetry. AAP was irreversibly oxidized in, at least, one electrode step, with potentials lower than the potential at which oxygen evolution started. Electrochemical methods based on voltammetric techniques (DPV and CV) have been developed for AAP determination in commercial pharmaceutical drugs. AAP content in pharmaceuticals was determined on the base of dependences of current intensity (electroanalytical measurements) and absorbance (UV-VIS spectra). The obtained results using both methods were in good agreement. The validation of CV, DPV and spectrophotometric methods is also presented. Spectrophotometric and voltammetric responses linearly increased with increasing AAP concentrations, in the range from 0.2 to 5 mmol L-1, with a correlation coefficient of 0.997 (UV-VIS), 0.999 (CV) and 0.998 (DPV). Both electrochemical methods are simple, reliable and sufficiently accurate and precise for AAP quantification in commercial drug samples (tablets). The analysis took only 5 minutes of manual operation, including Pt electrode pre-treatment.